Preparation method of metasurface structure and metasurface structure

By spin-coating the inorganic glass material under normal temperature and pressure to form a protective layer, the problem of high-deep and aspect ratio nanostructure metasurface structures in the prior art is easily damaged during subsequent treatment, and a low-cost and high-performance protective effect is achieved.

CN119471865APending Publication Date: 2025-02-18SHPHOTONICS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936756.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Prior art When preparing metasurface structures with high-deep-dimensional nanostructures, it is difficult to find a balance between low-cost and high-performance protective layers, especially in subsequent packaging, testing, cutting and transportation, where nanostructures are susceptible to damage. .

Method used

By spin-coating the inorganic glass material under normal temperature and pressure to form a protective layer, instead of chemical vapor deposition of silica or spin-coated organic resin photoresist, the gaps of the nanostructure are filled to form protection with excellent temperature resistance and compatibility. layer.

Benefits of technology

It realizes efficient filling of nanostructure gaps under normal pressure and temperature, avoids the use of expensive vacuum equipment and toxic gases, reduces production costs and operational difficulties, and improves the versatility and operability of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119471865A_ABST
    Figure CN119471865A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a metasurface structure and the metasurface structure, the preparation method comprises a single-face preparation step of forming a metasurface on a process surface of a substrate, and the single-face preparation step comprises the following steps: S1, forming a plurality of nano structures on the process surface; s2, filling an inorganic glass material in gaps of the nano structure through a spin-coating process to form a protective layer, wherein the nano structure and the protective layer jointly form the metasurface; filling can be carried out under the conditions of normal pressure and normal temperature, the filling performance is good, expensive vacuum equipment and toxic gas are avoided, operation is easy, the cost is low, and the universality and operability of the preparation technology are improved. And moreover, the obtained inorganic glass layer serving as the protective layer has better temperature resistance and compatibility in a subsequent high-temperature process, can protect the nano structure from mechanical damage, and can be compatible with a subsequent optical coating or multi-layer structure processing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of micro-nano optics, and in particular to a preparation method of a super surface structure and a super surface structure. Background Art

[0002] Optical metasurface is a sub-wavelength artificial material that achieves multiple optical functions by controlling light intensity, phase, polarization, propagation direction and other properties through a large number of high aspect ratio nanostructures. It has broad application prospects in optical devices, sensing, imaging, and display.

[0003] The aspect ratio of nanostructures is usually more than 7:1 or even 10:1. How to effectively protect nanostructures and other micro-nano structures with high aspect ratios during subsequent packaging, testing, cutting and transportation has become an important issue of concern in the industry. At the same time, process cost and feasibility are also key factors that must be considered in actual production and R&D.

[0004] In the prior art, protective materials are generally filled in the gaps between nanostructures with high aspect ratios to effectively protect the micro-nanostructures. However, when silicon dioxide is selected as the protective material, chemical vapor deposition is generally used. Chemical vapor deposition requires the use of various electronic special gases under vacuum conditions to react chemically to form a silicon dioxide film. In order to avoid the appearance of holes or gaps when filling nanostructures with high aspect ratios, special technologies and equipment such as high-density plasma chemical vapor deposition, sub-normal pressure chemical vapor deposition, fluid chemical vapor deposition, and atomic layer deposition are often required. These vacuum equipment are often expensive and are only applicable to ultra-large-scale integrated circuit production lines. The toxic and harmful gases used also require professional systems for processing, which have complex process flows, high costs, low efficiency, and are not environmentally friendly. Therefore, the commonly used method for forming a protective layer is to spin-coat the organic material SU-8, which is cured after baking and ultraviolet light. However, the organic material SU-8 can only withstand a maximum temperature of 200°C, and there is a relatively large difference in thermal expansion coefficient between it and the inorganic optical film, making it difficult to perform subsequent optical coating or multi-layer super-surface processing on the basis of SU-8.

[0005] Therefore, the preparation method of the super surface structure in the prior art has obvious limitations in balancing low cost and high performance protective layer. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a super surface structure and a super surface structure.

[0007] To achieve the above-mentioned invention object, the present invention adopts the following technical solution: a method for preparing a super surface structure, comprising a single-side preparation step of forming a super surface on a process surface of a substrate, the single-side preparation step comprising:

[0008] S1: forming a plurality of nanostructures on the process surface;

[0009] S2: filling inorganic glass material in the gaps of the nanostructures by a spin coating process to form a protective layer, wherein the nanostructures and the protective layer together form the super surface.

[0010] As a further improved technical solution of the present invention, step S2 specifically includes the following steps:

[0011] Fixing another surface of the substrate opposite to the process surface on a turntable;

[0012] While spraying the inorganic glass material onto the process surface, controlling the turntable to rotate until the inorganic glass material forms a liquid film layer on the process surface;

[0013] Heating the substrate on which the liquid film layer is formed so that the liquid film layer becomes a solid film layer;

[0014] Annealing is performed to form the protective layer.

[0015] As a further improved technical solution of the present invention, "while spraying the inorganic glass material onto the process surface, controlling the turntable to rotate until the inorganic glass material forms a liquid film layer on the process surface" is specifically:

[0016] While spraying the inorganic glass material onto the process surface, the turntable is controlled to rotate at a first preset speed;

[0017] Then, the turntable is controlled to rotate at a second preset speed until the inorganic glass material forms a liquid film layer on the process surface;

[0018] The first preset rotation speed is less than the second preset rotation speed.

[0019] As a further improved technical solution of the present invention, the first preset rotation speed is: 300-500 rpm; the second preset rotation speed is: 1500-5000 rpm.

[0020] As a further improved technical solution of the present invention, the inorganic glass material includes an organic solvent and a silicon compound dissolved in the organic solvent, and the boiling point of the organic solvent is 150°C to 200°C.

[0021] As a further improved technical solution of the present invention, the concentration of the silicon compound in the inorganic glass material is 3% to 15%.

[0022] As a further improved technical solution of the present invention, the viscosity value of the inorganic glass material is 1 to 2 cp.

[0023] As a further improved technical solution of the present invention, "fixing the other surface of the substrate opposite to the process surface on the turntable" specifically is fixing the other surface of the substrate opposite to the process surface on the turntable by vacuum adsorption.

[0024] As a further improved technical solution of the present invention, the thickness of the protective layer is 100-300nm.

[0025] As a further improved technical solution of the present invention, a laminated protective layer is obtained by repeating step S2 multiple times, and the thickness of the laminated protective layer is adapted to the size of the nanostructure.

[0026] As a further improved technical solution of the present invention, the substrate includes two opposite process surfaces, and the super surface is formed on the two process surfaces in sequence through the single-sided preparation step.

[0027] In order to achieve the above-mentioned object of the invention, the present invention also provides a supersurface structure, which is prepared by the above-mentioned supersurface structure preparation method.

[0028] The beneficial effects of the present invention are as follows: in the preparation method of the super surface structure of the present invention, after the processing of the nanostructure array is completed on the process surface of the substrate, a protective layer is formed by spin coating an inorganic glass material at room temperature and pressure, and filling can be carried out under normal pressure and temperature conditions, with good filling performance, avoiding expensive vacuum equipment and toxic gases, easy operation and low cost, and improving the versatility and operability of the preparation process; and the obtained inorganic glass layer as a protective layer has better temperature resistance and compatibility in subsequent high-temperature processes, which can not only protect the nanostructure from mechanical damage, but also be compatible with subsequent optical coating or multi-layer structure processing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a flow chart of the method for preparing the super surface structure in the present invention;

[0030] Figure 2 yes Figure 1 Flow chart of step S2 in FIG. DETAILED DESCRIPTION

[0031] The present invention will be described in detail below in conjunction with the various embodiments shown in the accompanying drawings. Figure 1 to Figure 2 It should be noted that these embodiments are not limitations of the present invention, and any equivalent transformation or replacement of functions or structures made by ordinary technicians in the field according to these embodiments shall fall within the protection scope of the present invention.

[0032] It should be understood that terms such as “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof, nor do they exclude the existence or addition of one or more other steps or combinations thereof.

[0033] Please refer to Figure 1-2 As shown, the present invention provides a method for preparing a supersurface structure and a supersurface structure prepared by the preparation method, wherein the supersurface structure includes a substrate, a supersurface located on at least one side of the substrate, and the supersurface includes a plurality of nanostructures and a protective layer filling in the gaps between the nanostructures.

[0034] The substrate may be a glass substrate or a silicon substrate. The nanostructure may be formed into a columnar shape and have a sub-wavelength size. The basic shape formed by projecting the nanostructure onto one side of the substrate may be extended from a circle, a round hole, a square, a square hole, etc. to a free geometric figure.

[0035] The side of the substrate having the metasurface is defined as the process surface. When the metasurface is provided on only one side of the substrate, that is, when the metasurface structure is a single-sided metasurface structure, the substrate has only one process surface, such as when the metasurface is provided on only the front side of the substrate, the front side of the substrate is the process surface, and when the metasurface is provided on only the back side of the substrate, the back side of the substrate is the process surface; when the metasurface is provided on both the front and back sides of the substrate, that is, when the metasurface structure is a double-sided metasurface structure, both the front and back sides of the substrate are the process surfaces.

[0036] The preparation method of the metasurface structure includes a single-sided preparation step of forming a metasurface on a process surface of a substrate. When the metasurface structure is a single-sided metasurface structure, the single-sided preparation step can be used to form a metasurface on a corresponding process surface; when the metasurface structure is a double-sided metasurface structure, both the front and back sides of the substrate are process surfaces, and the metasurface is formed on the two process surfaces in sequence through the single-sided preparation step, that is, after forming a metasurface on one of the front and back sides through the single-sided preparation step, the single-sided preparation step is repeated to form a metasurface on the other of the front and back sides.

[0037] Combination Figure 1 As shown, the single-sided preparation step includes:

[0038] S1: forming a plurality of nanostructures on the process surface;

[0039] S2: filling inorganic glass material in the gaps of the nanostructures by a spin coating process to form a protective layer, wherein the nanostructures and the protective layer together form the super surface.

[0040] Through the above steps, the processing of the nanostructure array is first completed on the process surface of the substrate to achieve the regulation of the intensity, phase or polarization of light. Since the nanostructure usually has a high aspect ratio (up to 7: 1 or even more than 10: 1), it is easily damaged in the subsequent testing, cutting and packaging processes, so it is necessary to fill it with a protective layer. In the present invention, by spin-coating an inorganic glass material at normal temperature and pressure to form a protective layer instead of chemical vapor deposition of silicon dioxide or spin-coating an organic resin photoresist, it can be filled under normal pressure and temperature conditions, with good filling properties, avoiding expensive vacuum equipment and toxic gases, easy to operate and low cost, and improving the versatility and operability of the preparation process; and the obtained inorganic glass layer as a protective layer has better temperature resistance and compatibility in subsequent high-temperature processes, which can not only protect the nanostructure from mechanical damage, but also be compatible with subsequent optical coating or multilayer structure processing technology.

[0041] The nanostructure processing technology in step S1 can adopt the existing nanostructure processing technology, such as photolithography technology, etc. Here, no further details are given.

[0042] Combination Figure 2 As shown, in some optional implementations, step S2 specifically includes the following steps:

[0043] S21: fixing the other surface of the substrate opposite to the process surface on a turntable;

[0044] S22: while spraying the inorganic glass material onto the process surface, controlling the turntable to rotate until the inorganic glass material forms a liquid film layer on the process surface;

[0045] S23: heating the substrate on which the liquid film layer is formed, so that the liquid film layer becomes a solid film layer;

[0046] S24: Annealing to form the protective layer.

[0047] In step S2, the inorganic glass material includes an organic solvent and a silicon compound dissolved in the organic solvent, wherein the silicon compound includes but is not limited to disiloxane SiH 3 -O-SiH 3 、Trisiloxane SiH 3 -O-SiH 2 -O-SiH 3 , cyclotetrasiloxane (H 2 SiO) 4 That is, the inorganic glass material is a liquid inorganic glass material, so that during the spin coating process, according to the principle of fluid mechanics, the inorganic glass material can cover the process surface and fill in the gaps of the nanostructure.

[0048] In a specific embodiment, the boiling point of the organic solvent is 150°C to 200°C. For example, propylene glycol methyl ether acetate (PGMEA), ethylene glycol methyl ether acetate (EGMEA), ethylene glycol propyl ether (EGPEA), etc. By using an organic solvent with a low boiling point, the organic solvent in the inorganic glass material can be fully volatilized at 150°C to 200°C. After a liquid film layer is formed on the process surface, the organic solvent in the liquid inorganic glass material can be volatilized by heating at a relatively low temperature to form a preliminarily solidified solid film layer.

[0049] In this embodiment, by fixing the substrate on a turntable, while spraying the inorganic glass material on the process surface through the glue dripping equipment, the substrate can be driven to rotate by driving the turntable to rotate, so that the inorganic glass material can be evenly distributed on the process surface during the rotation to form a liquid film layer; at the same time, the organic solvent is removed by heating and then annealed, so that the silicon compound undergoes a cross-linking reaction at high temperature, and a dense silicon dioxide film can be formed in the gap of the nanostructure, that is, a protective layer with excellent temperature resistance and physical stability is formed. Compared with conventional chemical vapor deposition, this embodiment avoids the generation of expensive vacuum equipment and toxic gases, and the process is simple and operable; compared with organic photoresist materials, the silicon dioxide film obtained by spin coating is more compatible and reliable in subsequent optical coating or other high-temperature processes, thereby providing a low-cost and temperature-resistant protective layer for high aspect ratio ultra-surface nanostructures. The protective layer obtained by the above method can effectively protect the nanocolumn structure during the subsequent flipping, cutting, packaging, and transportation processes, and the overall processing efficiency is high and the cost is controllable.

[0050] In a specific embodiment, step S21 specifically fixes the other surface of the substrate opposite to the process surface on a turntable by vacuum adsorption. When the metasurface structure is a single-sided metasurface structure, the other surface of the substrate opposite to the process surface is fixed to the turntable, and steps S22 to S24 are performed on the process surface. When the metasurface structure is a double-sided metasurface structure, such as preparing the front metasurface first and then the back metasurface, first fix the back of the substrate to the turntable, and perform steps S22 to S24 on the front of the substrate. After the front metasurface is prepared, fix the front metasurface to the turntable, and perform steps S22 to S24 on the back of the substrate.

[0051] Specifically, the turntable is provided with a vacuum suction cup, and the substrate is adsorbed on the turntable by the negative pressure of the vacuum suction cup. After the liquid film layer is formed, the pressure can be released by simply stopping the vacuum pump to remove the substrate with the liquid film layer from the turntable without damaging the formed liquid film layer. The operation is simple and the operability and yield of the preparation process are improved as a whole.

[0052] Specifically, the negative pressure of the vacuum chuck can be set to be 2KPa-4KPa lower than the standard atmospheric pressure. Of course, this is not limited to this. The greater the pressure difference, the stronger the adsorption capacity, thereby preventing the substrate from being eccentric or shaking during the spin coating process.

[0053] In some optional implementations, step S22 is specifically:

[0054] While spraying the inorganic glass material onto the process surface, the turntable is controlled to rotate at a first preset speed;

[0055] Then, the turntable is controlled to rotate at a second preset speed until the inorganic glass material forms a liquid film layer on the process surface;

[0056] The first preset rotation speed is less than the second preset rotation speed.

[0057] Through the above-mentioned double-stage rotation process, that is, first at a lower first preset speed, the spin-coated inorganic glass material is fully spread to cover the entire process surface, and then at a higher second preset speed, the excess inorganic glass material is removed and the thickness of the film layer is regulated to obtain a uniform and desired thickness of the liquid film layer, thereby forming a complete liquid film without obvious holes between the high aspect ratio nanostructures. After that, heating and curing and annealing are performed, so that the silicon compound can be cross-linked around the nanostructure to form a dense inorganic network. Compared with a single high-speed rotation or low-speed rotation, the double-stage rotation process can reduce edge accumulation and center defect problems, improve the coverage and uniformity of the protective layer, and make it difficult for subsequent packaging, transportation and double-sided processes to damage the super surface structure. Therefore, this embodiment can achieve effective filling of the nanostructure gap under normal temperature and pressure conditions, cooperate with the subsequent annealing process to form a protective layer with better temperature resistance, and also greatly reduce the production cost and operation difficulty relative to chemical vapor deposition or organic photoresist processes.

[0058] In a specific embodiment, the first preset speed is 300-500 rpm, such as 300 rpm, 400 rpm, 500 rpm, etc. The second preset speed is 1500-5000 rpm, such as 1500 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, etc. Of course, it is not limited thereto.

[0059] In some optional embodiments, the concentration of the silicon compound in the inorganic glass material is 3% to 15%, such as 3%, 10%, 15%, etc., which are not listed here. Within this concentration range, it can be ensured that the inorganic glass material contains sufficient precursor components, so that the inorganic glass material can fully penetrate and fill the gaps of the high aspect ratio nanostructure during spin coating, and the viscosity will not be too high to cause the formed liquid film layer to be uneven or difficult to coat.

[0060] In some optional implementations, the viscosity of the inorganic glass material is 1-2 cp. During the spin coating process, the inorganic glass material can more easily penetrate into the gaps of the nanostructures with a high aspect ratio and obtain a uniform liquid film layer.

[0061] Furthermore, in a specific embodiment of the present invention, the thickness of the protective layer formed in step S2 is 100 to 300 nm. That is, a single spin coating can usually achieve a protective layer thickness of 100 to 300 nm. If the thickness of the protective layer obtained after a single spin coating is thinner than the height of the nanostructure, that is, lower than the height of the nanostructure, a laminated protective layer can be obtained by repeating step S2 multiple times, and the thickness of the laminated protective layer is adapted to the size of the nanostructure. That is, after a layer of protective layer is formed by a spin coating-heating-annealing process, a spin coating-heating-annealing process is performed again on the basis of the protective layer to form a second layer of protective layer, and so on, to finally form a laminated protective layer.

[0062] The required protective layer thickness is formed by multiple stacking processes of spin coating, heating, and annealing. The laminated protective layer can not only meet the height requirements of the nanostructure, but also maintain the uniformity and density of the inorganic glass material, ensuring effective protection for the nanostructure during subsequent testing, packaging, and flipping. In this way, the thickness of the protective layer can be more flexibly adjusted, while avoiding problems such as deformation, discoloration, or decomposition of organic materials during high temperature or multi-layer processing, thereby further improving the overall reliability and compatibility of the metasurface structure.

[0063] Compared with the prior art, in the preparation method of the super surface structure in the present invention, after the processing of the nanostructure array is completed on the process surface of the substrate, a protective layer is formed by spin coating an inorganic glass material at room temperature and pressure, and filling can be carried out under normal pressure and temperature conditions, with good filling performance, avoiding expensive vacuum equipment and toxic gases, easy operation and low cost, and improving the versatility and operability of the preparation process; moreover, the obtained inorganic glass layer as a protective layer has better temperature resistance and compatibility in subsequent high-temperature processes, which can not only protect the nanostructure from mechanical damage, but also be compatible with subsequent optical coating or multi-layer structure processing technology.

[0064] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0065] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a super surface structure, characterized in that: The step of preparing a single surface of a substrate by forming a super surface on a process surface thereof comprises: S1: forming a plurality of nanostructures on the process surface; S2: filling inorganic glass material in the gaps of the nanostructures by a spin coating process to form a protective layer, wherein the nanostructures and the protective layer together form the super surface.

2. The method for preparing a super surface structure according to claim 1, characterized in that: Step S2 specifically includes the following steps: Fixing another surface of the substrate opposite to the process surface on a turntable; While spraying the inorganic glass material onto the process surface, controlling the turntable to rotate until the inorganic glass material forms a liquid film layer on the process surface; Heating the substrate on which the liquid film layer is formed so that the liquid film layer becomes a solid film layer; Annealing is performed to form the protective layer.

3. The method for preparing a super surface structure according to claim 2, characterized in that: “While spraying the inorganic glass material onto the process surface, controlling the turntable to rotate until the inorganic glass material forms a liquid film layer on the process surface” specifically means: While spraying the inorganic glass material onto the process surface, the turntable is controlled to rotate at a first preset speed; Then, the turntable is controlled to rotate at a second preset speed until the inorganic glass material forms a liquid film layer on the process surface; The first preset rotation speed is less than the second preset rotation speed.

4. The method for preparing a super surface structure according to claim 3, characterized in that: The first preset rotation speed is 300-500 rpm; the second preset rotation speed is 1500-5000 rpm.

5. The method for preparing a super surface structure according to claim 1, characterized in that: The inorganic glass material includes an organic solvent and a silicon compound dissolved in the organic solvent, and the boiling point of the organic solvent is 150° C. to 200° C.

6. The method for preparing a super surface structure according to claim 5, characterized in that: The concentration of the silicon compound in the inorganic glass material is 3% to 15%.

7. The method for preparing a super surface structure according to claim 5, characterized in that: The viscosity of the inorganic glass material is 1-2 cp.

8. The method for preparing a super surface structure according to claim 2, characterized in that: “Fixing the other surface of the substrate opposite to the process surface on the turntable” specifically means fixing the other surface of the substrate opposite to the process surface on the turntable by vacuum adsorption.

9. The method for preparing a super surface structure according to claim 1, characterized in that: The thickness of the protective layer is 100-300 nm.

10. The method for preparing a super surface structure according to claim 9, characterized in that: The laminated protective layer is obtained by repeating step S2 multiple times, and the thickness of the laminated protective layer is adapted to the size of the nanostructure.

11. The method for preparing a super surface structure according to claim 1, characterized in that: The substrate comprises two opposite process surfaces, and the super surface is formed on the two process surfaces in sequence through the single-side preparation step.

12. A super surface structure, characterized in that: The super surface structure is prepared by the super surface structure preparation method described in any one of claims 1 to 11.